Ameliorative Impact of Liraglutide on Chronic Intermittent Hypoxia-Induced Atrial Remodeling - Jun Wang; Yongzheng Liu; Changhui Ma; Yue Zhang; Meng Yuan; Guangping Li (Journal of Immunology Research)
Atrial fibrillation (AF) is the most frequent form of clinical cardiac arrhythmias. Previous evidence proved that atrial anatomical remodeling (AAR) and atrial electrical remodeling (AER) are crucial for the progression and maintenance of AF. This study is aimed at investigating the impact of the glucagon-like peptide-1 (GLP-1) receptor agonist, Liraglutide (Lir), on atrial remodeling (AR) mouse model induced by chronic intermittent hypoxia (CIH). C57BL/6 mice were categorized randomly into the control, Lir, CIH, and CIH+Lir groups. CIH was performed in CIH and CIH+Lir groups for 12 weeks. Lir (0.3 mg/kg/day, s.c) was administered to the Lir and CIH+Lir groups for four weeks, beginning from the ninth week of CIH. Meanwhile, echocardiography and right atrial endocardial electrophysiology via jugular vein, as well as induction rate and duration of AF, were evaluated. Masson and Sirius red staining assays were utilized to assess the extent of fibrosis in the atrial tissue of the mice. Immunohistochemical staining, RT-qPCR, and Western blotting were performed to evaluate the marker levels of AAR and AER and the expression of genes and proteins of the miR-21/PTEN/PI3K/AKT signaling pathway, respectively. ELISA was also performed to evaluate the changes of serum inflammatory factor levels. The CIH group exhibited significant AR, increased atrial fibrosis, and a higher incidence rate of AF compared to the control group. Lir could significantly downregulate the protein expression level in the PI3K/p-AKT pathway and upregulated that of phosphatase and tensin homolog deleted on chromosome ten (PTEN). Moreover, Lir downregulated the expression of miR-21. However, the protein expressions of CACNA1C and KCNA5 in atrial tissue were not changed significantly. In addition, Lir significantly attenuated the levels of markers of inflammation (TNF-α and IL-6) in the serum. In the mouse model of CIH, Lir treatment could ameliorate AR by the miR-21/PTEN/PI3K/AKT signaling pathway and modulation of inflammatory responses.